2022
DOI: 10.1149/1945-7111/ac8a1b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Tantalum Doped NMC811 and Its Impact on Crystal Structure and Electrochemical Performance at Higher Upper Cut-off Voltage

Abstract: Ni-rich, cathode active materials such as Li[Ni0.8Mn0.1Co0.1]O2 (NMC811) suffer from capacity fade, especially at higher upper cut-off voltages. There is an increasing interest on dopants such as Mo or Ta as a promising dopants for high-Ni materials. In this study four cathode active materials with Li[(Ni0.78Mn0.11Co0.11)1-xMx]O2 (NMC811, x=0, 0.005, 0.007, 0.013; M=Ta) were synthesized via a batch co-precipitation synthesis followed by calcination. To increase the probability of homogeneous distribution of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…It has previously been reported that Zr 4+ doping is associated with reduced primary particle size, 47 as are other dopants, mostly of higher valence state. 20,49,50,59 The observed restriction of grain growth can be explained by a dopant-induced change in surface energy, including segregation of dopant along grain boundaries. 17,59 This is not limited to battery materials, but can be applied to the sintering of ceramics in general.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has previously been reported that Zr 4+ doping is associated with reduced primary particle size, 47 as are other dopants, mostly of higher valence state. 20,49,50,59 The observed restriction of grain growth can be explained by a dopant-induced change in surface energy, including segregation of dopant along grain boundaries. 17,59 This is not limited to battery materials, but can be applied to the sintering of ceramics in general.…”
Section: Resultsmentioning
confidence: 99%
“…In various studies, it has been shown that a higher capacity retention of doped material correlates with a smaller particle or grain size relative to undoped material achieved by modification with high valence dopants. 20,49,50,59 In these cases, the smaller particle size resulted from dopant-induced grain growth suppression. In this work, a similar performance dependency on particle size is observed and especially clear in the comparison of impregnated and cocalcined LNO, while the surface impurities and their presence, respectively removal, may additionally affect the performance of coprecipitated LNO.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7] In order to further improve these materials and to reduce the intensity of bulk and surface degradation, doping and coating approaches are studied widely. [10][11][12][13][14][15][16][17][18][19][20][21] Recently, dopants with high oxidation states (e.g. Ta, Nb, W, Mo) were reported to be a promising solution, in that they reduce bulk degradation by adjustment of the primary-particle shape of the cathode.…”
mentioning
confidence: 99%